Evolution of Sustainability Reporting Research: Evidence from Indonesia (A Systematic Literature Review) - Inten Meutia; Shelly F. Kartasari; Hasni Yusrianti; Zulnaidi Yaacob (Universitas Pasundan, 2022)
This paper aims to systematize the research field of sustainability reporting (SR) in Indonesia. The paper reviews the development of research at SR, provides a critique of past research, and outlines future research opportunities. The paper provides a systematic review of existing studies and analyses SR in Indonesia using a qualitative approach. This review analyzed 36 studies on SR in Indonesia published between 2016 and 2020. Most published SR studies take a quantitative approach and focus on the private sector, with very little attention paid to SR implementation in the public sector or SMEs. Therefore, this study provides a comprehensive account of the development of sustainability reporting research in Indonesia over the past five years. The analysis undertaken in this paper addresses the gaps in the literature on SR research in Indonesia and serves as a guide for researchers, academics, and interested researchers. The study is limited to peer-reviewed papers, so research published at conferences or seminars is not addressed. However, further studies can be conducted by expanding the keyword and search database or using working papers from conferences or workshops to cover what this review may not have uncovered.